2022
DOI: 10.3390/ma15082754
|View full text |Cite
|
Sign up to set email alerts
|

Glass Fiber Reinforced Concrete as a Durable and Enhanced Material for Structural and Architectural Elements in Smart City—A Review

Abstract: The article highlights that glass fiber reinforced concretes (GFRC) can meet the requirements of Smart City better than ordinary concretes. The comprehensive discussion on GFRC composition is presented together with the review of glass fibers’ influence on various concrete properties. First of all, because of their bridging abilities, they can limit the width, length, and total area of cracks. Additionally, GFRC are characterized by enhanced tensile, flexural, and splitting strength; impact, abrasion, spalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…Both in structural materials, and items associated with the construction process. In addition, modest architectural features, are being manufactured with GF to create more appealing, durable, and safer public places [ 104 ]. Glass fiber-reinforced polypropylene composites are becoming more popular in the automobile sector due to their good mechanical qualities, ease of fabrication, lightweight, and low cost [ 101 ].…”
Section: Application Glass Fibersmentioning
confidence: 99%
“…Both in structural materials, and items associated with the construction process. In addition, modest architectural features, are being manufactured with GF to create more appealing, durable, and safer public places [ 104 ]. Glass fiber-reinforced polypropylene composites are becoming more popular in the automobile sector due to their good mechanical qualities, ease of fabrication, lightweight, and low cost [ 101 ].…”
Section: Application Glass Fibersmentioning
confidence: 99%
“…Hybrid reinforcement and reinforcement of different sizes and levels are increasingly used, for example, in modern composite materials and concretes, ranging from nanoscale reinforcement [8][9][10][11][12] to macroscale reinforcement [13][14][15]. Fiber reinforced concrete (FRC) [16][17][18] is developed by adding reinforcement to the concrete in form of fibers with different materials [19][20][21][22] and forms [23,24]. Short fibers can easily penetrate into concrete while mixing and these are added as a reinforcement so that the fibers will distribute throughout the concrete [25,26] and increases its load bearing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Rosas M. et al [26] found that the addition of GF to concrete enhances the tensile and flexural strength of concrete. Several scholars [27][28][29] have also examined the impact of GF on concrete workability from various perspectives. Li Y. et al [30] explored the advantages of BF when used in concrete, focusing on the study of concrete durability.…”
Section: Introductionmentioning
confidence: 99%